Education for the Young Generation : The Meeting Point of Religious Education and Maturity - Manullang, Megawati (LP. Ma'arif Janggan Magetan, 2021)
As a unit of Christian education, the church becomes an institution that bears responsibility and is a solution to problems that occur in society. The problem arises because there is no structured pattern of education that views poverty as a form of insensitivity to its role on earth. This study aims to prove the importance of religious education in a metaformative context to the maturity of the younger generation. The method chosen in this study is quantitative research with survey methods. Acting as a population are Tarutung State Institute for Christian Studies students, with a sample of 100 people. It is found that the value of Sig. (2-tailed) is 0.000 < 0.05, and indicated that there was a significant average difference between pre-tests and post-test results, which means religious education is effective for increasing the maturity of the younger generation.